Analysis of precision and accuracy of Precipitable Water Vapour derived from GPS observations - IGONDOVÁ, Miroslava (Contributions to Geophysics and Geodesy, 2009)
A Precipitable Water Vapour (PWV ), one of the parameters deﬁning an instant state of troposphere, can be derived from the combination of GPS observations and ground meteorological measurements. The precision of the PWV values depends on many variables used in the computation. Their inﬂuence is discussed and analysed. The accuracy of the GPS based PWV values is estimated by comparison to the radiosonde based PWV values within the period 2004–2007. Due to diﬀerent behaviour of the PWV with respect to time of the year, the analysis is performed in each season separately.